Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Uang Elektronik pada Aplikasi OVO - Multhazam, Riana; Marhawati, Marhawati; Hasan, Muhammad; Mustari, Mustari; Said, Muh. Ihsan (Business and Accounting Education Journal, 2021)
The purpose of this study is to analyze the trust, convenience, and promotion of the interest of economic education students to use electronic money in the OVO application. This research includes quantitative research. The population in this study were students of Economics Education FE UNM Class of 2015-2020, and samples were taken as many as 61 people with the snow balling technique. Data were collected by questionnaire. The research data were analyzed by multiple linear regression analysis. The results showed that trust, convenience, and promotion had an effect on interest in using the OVO electronic money application, either partially or simultaneously.